Metabolic Dysfunctions of Intestinal Fatty Acids and Tryptophan Reveal Immuno-Inflammatory Response Activation in IgA Nephropathy - Wu, Hongwei; Tang, Donge; Yun, Manhua; Liu, Haiping; Huang, Shaoxing; Yun, Chen; Hocher, Berthold; Zhang, Xinzhou; Liu, Fanna; Yin, Lianghong; Dai, Yong (Frontiers in Medicine, 2022)
Background: Immunoglobulin A nephropathy (IgAN) is the most common form of primary glomerulonephritis. Although an important link between intestinal metabolites and immune activity is widely established, the metabolic profile of IgAN is still poorly understood, which severely limits the mechanistic studies and therapy of IgAN. Methods: The diversity of intestinal flora and relative abundance of metabolites in IgAN patients and healthy subjects were measured by 16s ribosomal RNA gene sequencing combined with liquid chromatography tandem-mass spectrometry. The levels of serum Gd-IgA1, IL-6, IL-10, IL-22, and TNF-a were tested by ELISA. We employed the tryptophan-targeted UHPLC-MRM-MS approach to assess the content of tryptophan metabolites quantitatively. Results: Intestinal fatty acid levels, mainly unsaturated fatty acids, were observed to be dramatically decreased in IgAN patients. Disorders in linoleic acid and arachidonic acid metabolism, metabolic imbalances of anti-/pro- inflammatory fatty acid metabolites, and intestinal AhR signaling deficiency might reflect the damage of the intestinal mucosal barrier in IgAN patients. In addition, we found that high levels of Gd-IgA1, IL-22, and TNF-α were associated with the activity of the tryptophan-kynurenine metabolic pathway, as well as lower levels of 3-indolepropionic acid. 3-indolepropionic acid, kynurenine, and indoleacrylic acid had synergistic effects on regulating immuno-inflammatory responses in IgAN patients. Conclusions: The metabolic characteristic of fatty acids and tryptophan in the intestinal system is disturbed in IgAN patients, leading to active immune-inflammatory reactions.